2020
DOI: 10.1021/acsomega.0c05623
|View full text |Cite
|
Sign up to set email alerts
|

Disulfide Cross-Linked Poly(Methacrylic Acid) Iron Oxide Nanoparticles for Efficiently Selective Adsorption of Pb(II) from Aqueous Solutions

Abstract: The efficient selectivity of heavy metal ions from wastewater is still challenging but gains great public attention in water treatment on a world scale. In this study, the novel disulfide cross-linked poly(methacrylic acid) iron oxide (Fe 3 O 4 @S-S/PMAA) nanoparticles with selective adsorption, improved adsorption capability, and economic reusability were designed and prepared for selective adsorption of Pb(II) ions in aqueous solution. In this study, nuclear magnetic resonance, dynamic light scattering, scan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Functionalized with PAA improves the chelating capability of MNPs due to the presence of multiple polar carboxylic groups which is capable to form complexes with metal cations and adsorb heavy metals including Pb 2+ ions through ion exchange [44,45].The binding affinity of CR towards Pb 2+ ions doubles the removal efficiency of MNP/PAA adsorbent with high removal efficiency of >82 % after five cycles which makes them highly effective and economical adsorbent for lead ion removal. R.Wang et al prepared Fe3O4 nanoparticles using co-precipitation method and functionalization with poly(methacrylic acid) via free-radical copolymerization [46].Crystal structure close to that of magnetite is observed in both Fe3O4@MPS and Fe3O4@S-S/PMAA which is attributed by the characteristic diffraction peaks of the Fe3O4 in XRD patterns. SEM images of Fe3O4@S-S/PMAA nanoparticles showed microspherical structure having smooth surface, but an irregular rough morphology appeared for Fe3O4 and Fe3O4@MPS.…”
Section: Structural Features and Adsorption Mechanism Of "Pb" By Magn...mentioning
confidence: 99%
See 1 more Smart Citation
“…Functionalized with PAA improves the chelating capability of MNPs due to the presence of multiple polar carboxylic groups which is capable to form complexes with metal cations and adsorb heavy metals including Pb 2+ ions through ion exchange [44,45].The binding affinity of CR towards Pb 2+ ions doubles the removal efficiency of MNP/PAA adsorbent with high removal efficiency of >82 % after five cycles which makes them highly effective and economical adsorbent for lead ion removal. R.Wang et al prepared Fe3O4 nanoparticles using co-precipitation method and functionalization with poly(methacrylic acid) via free-radical copolymerization [46].Crystal structure close to that of magnetite is observed in both Fe3O4@MPS and Fe3O4@S-S/PMAA which is attributed by the characteristic diffraction peaks of the Fe3O4 in XRD patterns. SEM images of Fe3O4@S-S/PMAA nanoparticles showed microspherical structure having smooth surface, but an irregular rough morphology appeared for Fe3O4 and Fe3O4@MPS.…”
Section: Structural Features and Adsorption Mechanism Of "Pb" By Magn...mentioning
confidence: 99%
“…(g) adsorption kinetics as a function of adsorbent amount and(h) adsorption kinetics as a function of contact time for Pb(II) removal. (Reprinted with permission from [46] Copyright © 2020, Open access American Chemical Society).FSEM images of (i) Fe3O4 MNPs and (j) Fe3O4-SiO2-GSH MNPs; (k) adsorption kinetics as a function of Fe3O4-SiO2-GSH adsorbent amount and (l) adsorption kinetics as a function of initial Pb(II) concentration at pH 5.5, contact time: 120 min, T 35°C. (Reprinted with permission from [47]Copyright © 2016 Taiwan Institute of Chemical Engineers.…”
Section: Structural Features and Adsorption Mechanism Of "Pb" By Magn...mentioning
confidence: 99%
“…In polar solvents such as water, their ionizable groups can dissociate, resulting in the formation of charges on the polymer chains and the release of counterions in solution. Examples of polyelectrolytes include polystyrene sulfonate [2], polyacrylic acid (PAA) [11], and polymethacrylic acids [12], and their salts, DNA and other polyacids and polybases [13]. In particular, the study in MNP surface modification with PAA has been much reported recently [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, a novel Co(II)-imprinted polymer was prepared using magnetic Fe 3 O 4 NPs modified with tetraethyl orthosilicate and methacryloxy propyl trimethoxyl silane as the support. The easy separability was one of the advantages of magnetic materials for waste water treatment, and the magnetic materials had a unique role of rapid separation and recovering by applying an external magnetic field [18]. Bis(2-methacryloxyethyl) phosphate (B-2MP) and glycylglycine (GG) were used as dual monomers.…”
Section: Introductionmentioning
confidence: 99%